PEMBERIAN NUTRISI GOODPLANT PADA BERBAGAI UMUR BIBIT SECARA HIDROPONIK SISTEM NFT TERHADAP HASIL TANAMAN SELADA MERAH - ANAK AGUNG GEDE PUTRA; PANDE GEDE GUNAMANTA; KETUT TURAINI INDRA WINTEN (GANEC SWARA, 2021)
Research on the provision of Good plant nutrition at various ages of seeds using hydroponics NFT systems on the yield of red lettuce plants. This research is conducted in the experimental garden of the Faculty of Science and Technology, Tabanan University from October 2019 to December 2019. This research used a randomized block design (RBD). The experimental treatments consisted of 2 factors, namely the dose of Good plant nutrition and the age of the seeds. The first factor is the provision of a dose of Good plant (N) nutrition consisting of N1 = 800 ppm; N2 = 1000 ppm; N3 = 1200 ppm, and the second factor is the age of the seedlings (U) consisting of U1 = age 10 days after seeding (hss); U2 = Age 15 days after seeding (HSS), each treatment was repeated four times      The interaction between Good plant nutrient dose treatment and seedling age (N x U) had a very significant effect (P <0.01) on all observed parameters. The highest oven-dry weight of economic yields is achieved by the treatment of the Good plant nutrient dose of 1000 ppm at the age of 15 hss (N2U2) seeds, namely 5.24 g, an increase of 57.33% from the lowest weight achieved by the treatment of 1200 ppm Good plant nutritional dose at 10 hss (N3U1) ) namely 3.33 g.